2015
DOI: 10.7314/apjcp.2015.16.10.4219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydronephrosis on Survival in Advanced Stage Cervical Cancer

Abstract: Background: Hydronephrosis is frequently encountered in advanced stage cervical cancers, and may be associated with mortality. In the present study, we aimed to demonstrate the effect of hydronephrosis on survival in patients with inoperable advanced stage cervical cancer. Materials and Methods: The study data were acquired by retrospective analysis of the patient records belonging to 165 women with FIGO (International Federation of Gynecology and Obstetrics) stage-IIIB or more advanced cervical cancer, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Their 3-year survival rates were 37% and 74%, respectively, for those with and without UHN (p=0.002). These results are also similar to a study by Goklu et al [11] which showed that for patients with hydronephrosis, the mean survival was significantly shortened (p<0.05). However, there was no significant difference in survival between patients with bilateral and unilateral hydronephrosis (p>0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Their 3-year survival rates were 37% and 74%, respectively, for those with and without UHN (p=0.002). These results are also similar to a study by Goklu et al [11] which showed that for patients with hydronephrosis, the mean survival was significantly shortened (p<0.05). However, there was no significant difference in survival between patients with bilateral and unilateral hydronephrosis (p>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of urological complications was 45.9% in the present study, close to the 48.8% found by Atuhairwes et al [3]. Similarly, Lee et al [10] and Gloku et al [11] reported prevalences of urological complications of 55.8% and 44.8%, respectively. The high proportion of urological complications such as hydronephrosis is due to our study's high proportion of advanced stages.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The severity of hydronephrosis and its impact on overall survival was not evaluated among the included articles, however, Goklu et al observed that the mean survival of patients with unilateral hydronephrosis was significantly larger compared to that of patients with bilateral hydronephrosis (42.2 vs 29.9 months). 18 Patel et al reported that the most prominent symptom of hydronephrosis was urinary tract infection (9 out of 17 patients), accompanied by pain (8 out of 17 patients). 17 In their series they observed that 7 patients developed renal failure with creatinine levels that ranged between 1.7 and 5.6 mg/dL.…”
Section: Resultsmentioning
confidence: 99%
“…While these issues undoubtedly adversely affect quality of life, they also may be negatively correlated with survival. For example, two retrospective studies have demonstrated poorer OS among patients with stage IIIB-IVB cervical cancer and hydronephrosis at the time of diagnosis [5,6]. Higher symptom burdens in these women may also negatively impact their disease course.…”
Section: Discussionmentioning
confidence: 99%